The Relationship between Computed Tomography Pulmonary Angiography Findings and Right Ventricular Dysfunction in Patients with Pulmonary Embolism - In, Erdal; Turgut, Teyfik; Kalkan, Mehmet; Karadag, Muge Otlu; Dagli, Mustafa Necati (Bilimsel Tip Publishing House, 2014)
OBJECTIVES: In this study, we aimed to localize thrombus and to evaluate the relationship between the site of thrombus and right ventricular dysfunction (RVD) in patients with pulmonary embolism (PE) diagnosed with computed tomography pulmonary angiography (CTPA). MATERIAL AND METHODS: CTPA and echocardiography (ECHO) findings of 59 patients (35 male, 24 female) with PE diagnosed on CTPA were analysed retrospectively. The site of thrombus on CTPA was documented. Patients were divided into 2 groups according to ECHO findings as patients without RVD (group 1) and with RVD (group 2). RESULTS: The most frequent sites of thrombus formation were the right main pulmonary artery (33.8%) and right lower lobar artery (30.5%). It was observed that thrombus formation was significantly higher in the right system than that of the left (63.8% and 36.2%, respectively; p< 0.01). ECHO findings revealed that 16 of the 59 patients had RVD. The number of patients who had thrombus in the right main pulmonary artery was significantly higher in group 2 (p< 0.001). Pulmonary trunk diameter measured by CT was significantly lower in group 1 (28 mm +/- 3.61) in comparison to that in group 2 (37 mm +/- 5.88) (p< 0.01). Systolic pulmonary artery pressure was significantly positively correlated with pulmonary trunk and right ventricular diameter (p< 0.001). Sensitivity, specificity and positive predictive value of CTPA in detecting RVD were 87.5% (14/ 16), 95.3% (41/ 43) and 87.5% (14/ 16), respectively. CONCLUSION: It was observed that the probability of RVD was higher in patients with thrombus in right main pulmonary artery. There was a strong relationship between the pulmonary trunk and right ventricular diameter measured by CT and RVD observed on ECHO. It was suggested that CTPA is a reliable imaging method for detecting RVD in patients with PE.
Keywords: Pulmonary embolism; echocardiography; tomography